An examination of present research on the female entrepreneur — Suggested research strategies for the 1990's - Moore, Dorothy P. (Journal of business ethics, 1990)
Intensive investigations into female entrepreneurships are a relatively recent research phenomenon. Advances in the past five years, while dramatic, find the field in an initial stage of paradigm development. Individual studies appear fragmented, unrelated, and seem to describe only small segments of the female entrepreneurial population and more frequently than not apply theoretical tools developed in other areas which are neither reliable or valid. This article examines a number of current research and methodological issues, presents a descriptive analysis of the traditional and modern female entrepreneur, suggests focal areas for research oriented toward the establishment of typologies, models and theory development.